ANALYSIS OF DATA PROCESSING SYSTEMS FOR ORDER FLOWER ON FLOWER SHOP "ANITA FLORIST" - Jon Erikson Simorangkir; Irwan Numara, Ir, MM (Jurnal Sistem Informasi, 1998)
The use of computers as a tool in data processing has indeed been felt by manyvarious applications, the information needed can be produced quickly, accurately andprecisely. With the implementation of computerized information systems in ShopFlorist "Anita's Florist" is expected to overcome the problems in the execution oftransactions for ordering products are used.The author has evaluated the implementation of new systems in data processing, willfacilitate the company in an efficient transaction process and better effectiveness.